Literasi Keuangan Dosen-Dosen Perguruan Tinggi di Palembang: Faktor Gender dan Usia - Soejono, Fransiska; Mendari, Anastasia Sri (Universitas Muhammadiyah Surakarta, 2018)
This study aims to measure the level of financial literacy of lecturers in Palembang. The method of analysis in this research is descriptive analysis. The number of respondents in this study were 153 respondents. Data collection techniques used survey techniques with questionnaires. Financial literacy index is determined through four stages: (1) Grouping of financial literacy variables in 2 groups, namely basic financial literacy and advanced financial literacy, (2) giving score 1 for correct answer and 0 for other answer that is unknow, wrong answer and refused to answer, (3) Calculate the weight of each variable by using simple weight, (4) Calculate index of financial literacy. The results showed that on average the basic financial literacy of lecturers in Palembang was included in the moderate category, while the average advanced financial literacy was in the low category. The level of financial literacy or Financial Literacy Index as a whole including the low category. Distribution of basic financial literacy based on gender and age average dominant in high category reverse dominant advanced financial literacy distribution in low category.